PENGARUH KEPUASAN KERJA DAN MOTIVASI TERHADAP PRODUKTIVITAS KERJA KARYAWAN EIGHTYEIGHT @KASABLANKA - Yunita; Prawoto (Human Capital Development, 2016)
Purpose- The purpose of this research is to know the job satisfaction and motivation effect simultaneously or partially to work productivity of employees. Design/methology/approach- The population in this research the employees of EIGHTYEIGHT@KASABLANKA. The sample that used for this research are 80 employees. Sensus sampling technical. Data analysis tools that used for this research are multi linear regression, validity test, realibility test, classic assumption test (normality test, multicollinearity test, heteroscedasticity test, and linearity test) whereas the hypothesis test including the F test, t test, partial correlation analysis and coefficient of determination (R2). Findings- The job satisfaction and motivation has an effect to work productivity of employees either partially or simultaneously. The jhob satisfactiotn with low category but real. The motivation also with the same effect in low category and real. However, by both of the varable simultaneously resuting in moderate category, and real. Research limitations- The limited sampel and variables were probably the limitation of this research.